ON THE USE OF PHRASEOLOGY IN WORKS OF ART (Based on the Novel "The Address of Justice" by Odil Yaqubov) - Magdaliyeva Khafiza Mirqadirovna, G'aniyeva Shohista Nuraliyevna (American Journals, 2023)
This article is intended for high school students to speak correctly, learn the difference between phrases and compound words, and ensure the accuracy of speech.
Keywords: phrase, compound word, address of justice, correctness of the word